Effects of Modified Sanzi Yangqin Decoction on Tyrosine Phosphorylation of IRS-1 in Skeletal Muscle of Type 2 Diabetic Rats - Wang, Ya (Evid Based Complement Alternat Med, 2018)
This study aimed to investigate the effect of Modified Sanzi Yangqin Decoction on tyrosine phosphorylation of insulin receptor substrate 1 (IRS-1) in skeletal muscle of type 2 diabetic rats. The rat model of type 2 diabetes was induced by high-fat diet and multiple low-dose streptozotocin injections. Diabetic model rats were randomly divided into 5 groups: the model control group, the metformin group, and Modified Sanzi Yangqin Decoction groups of low, medium, and high doses. OGTT was conducted every two weeks during treatment period. At the end of the treatment, the fasting blood glucose (FBG) level and the fasting C-peptide level were measured to calculate insulin resistance index. The levels of IRS-1, p-IRS-1((Tyr895)), and protein tyrosine phosphates 1B (PTP1B) in skeletal muscle were also measured. Modified Sanzi Yangqin Decoction significantly reduced the FBG level, increased the fasting C-peptide level, and lowered the insulin resistance index in type 2 diabetic rats. It also significantly increased the protein level of p-IRS-1((Tyr895)) and reduced the PTP1B protein level in skeletal muscle of type 2 diabetic rats. Modified Sanzi Yangqin Decoction increases tyrosine phosphorylation of IRS-1 in skeletal muscle of type 2 diabetic rats, which results from the increase of p-IRS-1((Tyr895)) protein and is related to the suppression of PTP1B protein.